Study on the packaging labels of chocolate product affecting Kelantan consumer - Adibah Hani Ahmad Zaidi (2016)
Chocolate packaging product plays an important role on pursuing consumers to purchase the products. The ﬁrst thing of consumers may look is the packaging characteristics. This research attempts to study the awareness of preferences packaging chocolate product that affecting Kelantan consumer. Besides, to examine the level of behavioural attitude, subjective norm, behavioural control, ability of Kelantan consumer towards the packaging of chocolate products. Based on this research, it can be says that mostly consumers attract to purchase the chocolate products based on the social’s inﬂuence around them. The study is carried out based on the 150 respondents of surveys with the 42 questions on Likert‘s scale which is distributed within Kelantan area. Cronbach’s Alpha, Keiser-Meyer Olkins, chi-square and measure of sampling adequacy are used to identify the acceptable limits. This study was determined ﬁve factors including the awareness, consumer attitude, social’s inﬂuence, the ability to purchase chocolate product and the intention to purchase chocolate packaging products.